Management of early-stage hepatocellular carcinoma: challenges and strategies for optimal outcomes - Jae Hyun Yoon; Sung Kyu Choi (Korean Liver Cancer Association, 2023)
Although hepatocellular carcinoma (HCC) is associated with a poor prognosis, management of early-stage HCC is often successful with highly efficacious treatment modalities such as liver transplantation, surgical resection, and radiofrequency ablation. However, unfavorable clinical outcomes have been observed under certain circumstances, even after efficient treatment. Factors that predict unsuitable results after treatment include tumor markers, inflammatory markers, imaging findings reflecting tumor biology, specific outcome indicators for each treatment modality, liver functional reserve, and the technical feasibility of the treatment modalities. Various strategies may overcome these challenges, including the application of reinforced treatment indication criteria with predictive markers reflecting tumor biology, compensation for technical issues with up-to-date technologies, modification of treatment modalities, downstaging with locoregional therapies (such as transarterial chemotherapy or radiotherapy), and recently introduced combination immunotherapies. In this review, we discuss the challenges to achieving optimal outcomes in the management of early-stage HCC and suggest strategies to overcome these obstacles.